Skill the low-skilled: the knowledge-driven stepwise migration of Vietnamese workers in South China - Kejie Huang; Tianlong You (Comparative Migration Studies, 2024)
Abstract This article investigates the interplay between knowledge acquisition and the stepwise migration trajectories of low-skilled Vietnamese workers in China. Utilizing a rich array of data garnered from face-to-face interviews, customized surveys, on-site observations, media narratives, and an archival review of government regulations in Guangxi—a province bordering Vietnam—and in Guangdong, a non-adjacent province, this study proposes an analytical framework, skill-driven migration, to highlight the synergy between the pre-migratory socio-demographic attributes of migrants and the circumstances prevailing in both the places of origin and destination which orchestrates distinct job allocations and skill augmentation avenues. Notably, our study underscores that the competencies acquired in manufacturing employments potentially broaden the horizon of destinations for migrants in their subsequent stepwise migration endeavors. This phenomenon, in turn, poses intricate immigration management quandaries for newly emerged destination nations like China, spotlighting a nuanced dimension of labor mobility and policy frameworks in the evolving regional economic integration. Last, our findings challenge the conventional dichotomy of high-skilled and low-skilled categories of labor migration, as well as the dichotomy of explicit-tacit knowledge.